Economic, Socio-Cultural, and Environmental Impacts on Community Support for Tourism: A Case in Harapan Island, Kepulauan Seribu - Levyda Levyda (Bina Nusantara University, 2020)
The research aimed to examine economic, socio-cultural, and environmental impacts on community support fortourism in Harapan Island, Kepulauan Seribu. Data were collected using a questionnaire. The population was thepeople of Harapan Island. Around 100 residents were selected as respondents through accidental sampling. Then,data were processed using Partial Least Squares Structural Equation Modeling (PLS-SEM) version 3.2.8. Basedon the hypothesis test, economic and socio-cultural factors significantly influence community support. Socioculturalfactors have the most significant effect on community support. Meanwhile, environmental factors do notaffect community support. The research contributes to the model of community support for the development oftourism on a small island. To increase community support, it is necessary to increase the income of the community,job opportunities, security, protection of traditional culture, and welfare.